(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
A women is a structure of any developing country .In our country however ,we have been struggle to protect female child and set right skewed sex ratios in all states .while women throughout the world have been carrying the credit of ushering in pioneering innovations , our women have a challenging time securing basics such as education and healthcare. Out of total population of the world more or less fifty percent is assumed to be men’s population and more or less is assumed to be women populace. So in India too. They are in this manner viewed at the better fifty percent of the general public. Prior to 18thcentury in India women were treated as inferior to men .The birth of a girl was unwelcomed, her marriage was a burden and if she became a widow then she was a considered inauspicious .In conventional social orders they have limited to the four dividers of house performing household exercises. Educational opportunities were restricted. In resent stage condition of women is supposed to be changed after various reforms , government had passed various enactment in order to uplift status of women.They have got a special space for themselves in the male ruled world. In today’s competitive world entrepreneurship plays a very important role in the growth ,development , enhancement of any county .Entrepreneurship is not just like a source of income only but it also represent how much creativity are there in any country .Like other organizations, institutions entrepreneurship helps in the empowerment of any society.